2013
DOI: 10.1097/ijg.0b013e318237c8c5
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Diagnostic Performance of GDxVCC and Spectralis OCT on Eyes With Atypical Retardation Pattern

Abstract: Diagnostic accuracy is comparable for SD-OCT and GDxVCC if typical scans (TSS=100) are investigated. Decreasing TSS is associated with a decrease in diagnostic accuracy for discriminating healthy and glaucomatous eyes by scanning laser polarimetry. NFI is less influenced than the global or sector retinal nerve fiber layer thickness. The TSS score should be included in the standard printout. Diagnostic accuracy of SD-OCT is barely influenced by low TSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…For this study we used the global RNFL thickness, which corresponds to the average RNFL thickness in the 3.4 mm diameter peripapillary circle around the optic nerve head. This parameter has been shown to perform well in the assessment of rates of change in previous studies 17, 20 .…”
Section: Methodsmentioning
confidence: 69%
“…For this study we used the global RNFL thickness, which corresponds to the average RNFL thickness in the 3.4 mm diameter peripapillary circle around the optic nerve head. This parameter has been shown to perform well in the assessment of rates of change in previous studies 17, 20 .…”
Section: Methodsmentioning
confidence: 69%
“…SLP results are largely influenced by the scan status [20] and the polarizing properties of the cornea and crystalline lens, which may lead to spurious measurements [21]. It was shown that SLP with variable corneal compensation, SLP with enhanced cornea compensation, and SD-OCT RNFL measurements cannot be directly compared [22].…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 47 48 ] Diagnostic accuracy has been found to be comparable for SD-OCT and GDx-VCC if typical scans (TSS = 100) are investigated. [ 53 ] Decreasing TSS is associated with a decrease in diagnostic accuracy for discriminating healthy and glaucomatous eyes by SLP. NFI has been found to be less influenced than the global or sector RNFL thickness.…”
Section: Atypical Retardation Patternsmentioning
confidence: 99%